1999
DOI: 10.1292/jvms.61.657
|View full text |Cite
|
Sign up to set email alerts
|

Serum alpha-fetoprotein Values in Dogs with Various Hepaic Diseases.

Abstract: ABSTRACT. Serum alpha-fetoprotein (AFP) values were measured in hepatic diseased dogs with or without tumor and non-hepatic tumor bearing dogs by a sandwich ELISA using anti-dog AFP antiserum. Serum AFP values were less than 70 ng/ml in clinically healthy dogs. The values in dogs with hepatocellular carcinoma were higher than 1,400 ng/ml in 7 of 9 dogs, wherever those in two dogs with cholangiocarcinoma were in the normal range. Serum AFP values in hepatic diseased dogs without tumor were also high, however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
0
16
0
2
Order By: Relevance
“…13 Subsequently, they found that, as in humans, AFP concentrations are elevated in canine tumors, especially in hepatocellular carcinoma (HCC). 12 In those reports, serum AFP was mildly elevated in some dogs with hepatic and nonhepatic diseases, even in those without tumors. A correlation between histopathology, immunohistochemistry, and serum AFP concentration in canine HCC has not been reported.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…13 Subsequently, they found that, as in humans, AFP concentrations are elevated in canine tumors, especially in hepatocellular carcinoma (HCC). 12 In those reports, serum AFP was mildly elevated in some dogs with hepatic and nonhepatic diseases, even in those without tumors. A correlation between histopathology, immunohistochemistry, and serum AFP concentration in canine HCC has not been reported.…”
mentioning
confidence: 88%
“…It has also been shown that the serum AFP concentration increases when normal hepatocytes are actively dividing, [9][10][11] and a moderate increase in serum AFP concentration is also reported in hepatic dysfunction or tumors other than HCC. 12 Therefore, quantification of serum AFP may not be used per se for a definitive diagnosis of HCC. In a previous study with a small population, 90% of dogs (19/21) with hepatic disease but without tumors were shown to have AFP concentrations of under 500 ng/ml, whereas 92% of tumor-bearing dogs (50/ 54) without hepatic tumors had concentrations of under 1,000 ng/ml.…”
mentioning
confidence: 99%
“…Hierzug ehören α -Fetoprotein, carcinoembryonic antigen (CEA), squamous cellcarcinoma antigen(SCC-antigen), Cytokeratin 19 fragments (CYFRA) und Carbohydrate antigen1 9-9 (CA19-9) (1,8,16). Beim Hund ließ sich bisherlediglichineini-genUntersuchungeneine gewisse Bedeutungvon α -Fetoprotein im Zusammenhangmit demLeberzellkarzinom, Gallengangskarzinom sowiedem malignen Lymphom derLeber nachweisen (13,18,20,33). Dieklinischeund diagnostische Relevanzdieses Tumormarkersi st für denH und jedochb is heute unklaru nd muss erst in weiterenStudienvalidiert werden.…”
Section: Introductionunclassified
“…There is a possibility that CD29, CD44, CD133 and Dlk-1 are expressed only in situations where liver regeneration is enhanced, as α-fetoprotein [19], when it might be difficult to distinguish between tumor and normal tissue using only these antigens. In the present study, these surface antigens were not assessed in liver tissue after hepatectomy or hepatitis, and further research is required to determine appropriate cancer cell markers.…”
mentioning
confidence: 99%